ASSESSMENT OF DROUGHT IN THE SOUTHERN SUB-REGION OF THE RED RIVER DELTA FOR AGRICULTURAL DEVELOPMENT - Ngoc Hung, Dao; Truong San, Nguyen; Thi Hai Yen, Ngo; Thi Phuong, Cu; Linh Trang, Hoang; Thi Tuyen, Tran; Hoang Hue, Hua; Thi Thuy Dung, Phan; Thi My Hien, Le (HNUE Journal of Science: Journal of Natural Sciences, 2025)
The southern sub-region of the Red River Delta possesses favorable natural conditions for agricultural development and plays an important role in the country’s agricultural output. Nevertheless, this region is highly vulnerable to natural disasters, particularly droughts, which pose significant challenges to agricultural productivity. This study applies a combination of statistical and spatial analysis methods to examine drought characteristics in the Southern Subregion of the Red River Delta. The research methodology included: (i) calculation of the K drought index, (ii) estimation of drought and extreme drought frequency, (iii) application of simple linear regression analysis, and (iv) interpolation using the Inverse Distance Weighting (IDW) method. Monthly precipitation and evapotranspiration data from 1991 to 2020 were utilized. The results show that droughts occurred in almost all months, except August and September, with the most severe events concentrated in December, January, and February. Although the region is relatively homogeneous, spatial variations are apparent. Ha Nam Province consistently recorded the lowest drought severity across all indicators, including drought frequency, extreme drought frequency, and the annual drought index. In contrast, a prominent elongated zone (or “trough”) with a high frequency of severe drought months is evident in the spatial distribution maps. Additionally, a drought tongue with increasing severity extends from Ha Nam in a northeast–southwest direction toward Van Ly (Nam Dinh). These findings provide critical insights for disaster risk reduction and serve as a scientific basis for agricultural planning and sustainable development in the region.